2021
DOI: 10.1186/s12887-021-02866-y
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide therapy for IgA vasculitis with nephritis in children

Abstract: Background Henoch-Schönlein purpura (HSP), also called IgA vasculitis, is a systemic vasculitis characterized by deposits of immunoglobulin A in blood vessels. Renal impairment of these patients is the main determinant of prognosis. The optimal treatment of HSP nephritis (HSPN) in children remains controversial, but many clinicians administer an immunosuppressive agent with a corticosteroid. A previous study reported that leflunomide (LEF) with a corticosteroid was effective for adult patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Leflunomide (LEF) is a comparatively new oral immunosuppressant that disrupts T and B cell function by inhibiting dihydronucleic acid dehydrogenase (the ratelimiting enzyme for ab initio synthesis of pyrimidine nucleotides), specifically inhibits T-dependent autoantibody formation; and a few tyrosine kinase signaling molecules involved in immune function are also inhibited by LEF (Siemasko et al, 1996;Lou et al, 2006). The current clinical trial results showed that LEF combined with steroids improved the renal prognosis of patients with IgAV nephritis with nephrotic proteinuria more significantly than steroids alone, with no apparent adverse effects (Zhang Y. et al, 2014;Hou et al, 2021). LEF, which has been reported to be rapidly biotransformed to its active metabolite, is usually undetectable in plasma and therefore has only a tiny in vivo exposure (and no pharmacological activity).…”
Section: Mizoribine and Leflunomidementioning
confidence: 83%
“…Leflunomide (LEF) is a comparatively new oral immunosuppressant that disrupts T and B cell function by inhibiting dihydronucleic acid dehydrogenase (the ratelimiting enzyme for ab initio synthesis of pyrimidine nucleotides), specifically inhibits T-dependent autoantibody formation; and a few tyrosine kinase signaling molecules involved in immune function are also inhibited by LEF (Siemasko et al, 1996;Lou et al, 2006). The current clinical trial results showed that LEF combined with steroids improved the renal prognosis of patients with IgAV nephritis with nephrotic proteinuria more significantly than steroids alone, with no apparent adverse effects (Zhang Y. et al, 2014;Hou et al, 2021). LEF, which has been reported to be rapidly biotransformed to its active metabolite, is usually undetectable in plasma and therefore has only a tiny in vivo exposure (and no pharmacological activity).…”
Section: Mizoribine and Leflunomidementioning
confidence: 83%
“…This finding is in line with several studies in which relapses occurred more frequently in children treated with an adjunctive steroid therapy [ 21 , 22 ]. Contrastingly, in Chen L et al study, corticosteroids improved the immune function of children with HSPN and promoted the recovery of renal function [ 23 ].In the same line, Hou et al successfully treated patients with HSPN by administering corticosteroid in combination with leflunomide therapy [ 24 ].Our controversial finding highlights the recommendation to limit the use of steroids to a carefully selected group of HSPN children, even though corticosteroids may alleviate the symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…We used pulse steroids in many cases with the above indications with positive results in decreasing IgA vasculitis symptoms. The use of methylprednisolone in pulse therapy to treat children with IgA vasculitis is not widely reported on, as most previous IgA vasculitis studies are case reports [ 40 , 41 , 42 ]. A large multicenter observational study of clinical outcomes in hospitalized children with new-onset HSP revealed that early corticosteroid exposure is associated with statistically significant decreased hazard ratios for surgery, endoscopy, and imaging [ 43 ].…”
Section: Discussionmentioning
confidence: 99%